Pengembangan E-Modul Eco-Enyzme untuk Mahasiswa MK Botani Ekonomi Hortikultura Prodi Pendidikan Biologi UNTAD - Lestari M. P. Alibasyah; Astija; Isnainar; Vita Indri Febriani; Akram; Dwi Setyorini (Postgraduate, University of Mataram, 2025)
Learning in the Economic Botany and Horticulture course is still dominated by lectures, resulting in limited student procedural skills and the absence of structured teaching materials. This study aims to develop and evaluate an eco-enzyme e-module to improve conceptual understanding, practical competence, and learning effectiveness. Using a Research and Development (R&D) approach with the ADDIE model, the study involved expert validation, a limited trial with one class, and pre-test/post-test assessment. Data was analyzed through descriptive validation scores, practicality ratings, and N-gain effectiveness. Results show that expert validation yielded very feasible scores for content (90%), media (88%), and instructional design (86%). The practicality test produced a very practical overall score of 87%, indicating high usability, readability, visual appeal, accessibility, and engagement. Implementation of the e-module increased students’ mean score from 62.4 (pre-test) to 91.2 (post-test), generating an N-gain of 0.77 categorized as high effectiveness. The e-module successfully integrates conceptual explanations, fermentation procedures, multimedia features, and project-based activities related to eco-enzyme production. In conclusion, the eco-enzyme e-module is valid, practical, and effective for supporting independent learning and enhancing students’ conceptual and procedural skills in accordance with the course learning outcomes.